Ответы и объяснения

  • Minsk00
  • почетный грамотей
2013-06-21T11:01:18+00:00

sin2x=cos3x 

Преобразуем cos в sin так как cos3x = sin(пи/2-3x)

 sin2x - sin(пи/2-3x) = 0

2sin((2x-(пи/2-3x))/2)*cos((2x+(пи/2-3x))/2) = 0

  sin((5x-пи/2)/2)*cos((-x+пи/2)/2) = 0

  sin(5x/2-пи/4)*cos(x/2 -пи/4) = 0 

  sin(5x/2-пи/4) = 0                                  cos(x/2-пи/4) = 0  

  5x/2-пи/4= пи*n                                     x/2-пи/4 = пи/2+пи*n

  x = 2пи*n/5+ пи/10                                 x=  3пи/2 + 2пи*n